2008
DOI: 10.1071/ar07193
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and physiological traits associated with high yield and stay-green phenotype in wheat

Abstract: Water availability is a key limiting factor in wheat production in the northern grain belt of Australia. Varieties with improved adaptation to such conditions are actively sought. The CIMMYT wheat line SeriM82 has shown a significant yield advantage in multi-environment screening trials in this region. The objective of this study was to identify the physiological basis of the adaptive traits underpinning this advantage. Six detailed experiments were conducted to compare the growth, development, and yield of Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 40 publications
7
129
1
Order By: Relevance
“…A functional stay-green trait enables the plant to synthesize and store greater levels of assimilates, which can lead to increased crop yields under certain environments (Richards 2000;Christopher et al 2008;Zhou et al 2011;Derkx et al 2012). Our photosynthesis measurements showed that the GPC-1 mutants maintain photosynthetic activity for longer than the control lines; hence we can classify the GPC-1 mutants as functional stay-green mutants.…”
Section: Stay-green Phenotype and Its Potential Effects On Yield Compmentioning
confidence: 86%
“…A functional stay-green trait enables the plant to synthesize and store greater levels of assimilates, which can lead to increased crop yields under certain environments (Richards 2000;Christopher et al 2008;Zhou et al 2011;Derkx et al 2012). Our photosynthesis measurements showed that the GPC-1 mutants maintain photosynthetic activity for longer than the control lines; hence we can classify the GPC-1 mutants as functional stay-green mutants.…”
Section: Stay-green Phenotype and Its Potential Effects On Yield Compmentioning
confidence: 86%
“…Zaman-Allah and colleagues (2011a) reached the same conclusion with twenty chickpea genotypes contrasting for terminal water stress tolerance. Nevertheless, the benefit of deeper root systems has been shown in other studies (Kirkegaard et al 2007;Christopher et al 2008;Hund et al 2009). For example, a simulation study indicated that maize yields would increase if the root depth increased (Sinclair and Muchow 2001).…”
Section: Usual Assumptions About Roots Under Water-limited Conditionsmentioning
confidence: 96%
“…Several authors have argued that the presence of small amounts of water during key crop stages such as the grain filling period would confer a major benefit (Ketring and Reid 1993;Christopher et al 2008;van Oosterom et al 2011). Unfortunately, it is difficult to measure water extraction precisely in the field, especially the small but key amounts that may be extracted during the grain filling period; however, a lysimetric method now exists in which a precise water extraction measurement is possible at all crop stages (e.g.…”
Section: The Need For Dynamic Measurements Of Water Extraction At Keymentioning
confidence: 99%
“…Certainly RUE levels during grain filling have improved (e.g. Miralles and Slafer 1997), and some modern varieties appear to show better 'stay green' (Christopher et al 2008). Finally it appears that grain-filling photosynthetic activity can actually be increased by a larger GN sink (see above).…”
Section: Grain Weightmentioning
confidence: 99%